The Sydney Mental Health Client Mortality Audit: what does it tell us and what are we to do?. (April 2014) - O'Connor, Nick; Hunt, Glenn E; O'Hara-Aarons, Maureen; Hall, Allan; Snars, Jeff; Storm, Victor; Lambert, Tim
Objectives: To examine the characteristics of those mental health clients of an Australian metropolitan health service who died during a 6 year period, 2005 – 2010. Methods: The medical records, and where available, coronial post-mortem examinations were audited for 109 people with schizophrenia who died while they were clients of the mental health service. Results: The mean age of death for men was 45 years and for women, 47 years, compared to the general population's male and female life expectancy of 79 and 84 years, respectively. About one-half of the deaths were due to suicide ( n = 55), followed by natural causes ( n = 42; 39%), undetermined causes ( n = 7), and accidents or acts of violence ( n = 5). Smoking rates, diagnosed diabetes and hypertension were higher in the group that died from natural causes. Morbid obesity (body mass index (BMI) > 35 kg/m 2 ) rates were higher in the group that died of natural causes (38%), compared with the suicide group (5%). Conclusions: While suicide accounts for the majority of those dying prematurely in this study cohort, it appears that for those who survive the risk of suicide in the earlier period of a chronic psychotic illness, there is yet another threat to life expectancy: death from preventable cardiorespiratory disorders, due to a poor lifestyle and social deprivation.